Solution:
"y(x)\\leftrightarrow Y(p)"
"y'(x)\\leftrightarrow pY(p)-y(0)=pY(p)-14"
"y''(x)\\leftrightarrow p^2Y(p)-py(0)-y'(0)=p^2Y(p)-14p-28"
We compose an operator equation that corresponds to the given differential equation:
"p^2Y(p)-14p-28-4(pY(p)-14)-96Y(p)=0"
"(p^2-4p-96)Y(p)=14p-28"
"Y(p)=(14p-28)\/(p^2-4p-96)"
"Y(p)=(14p-28)\/((p+8)(p-12))"
"y(x)=Res_{p=-8}(Y(p)e^{px})+Res_{p=12}(Y(p)e^{px})="
"=\\lim\\limits_{p\\rarr-8}\\frac{14p-28}{p-12}e^{px}+\\lim\\limits_{p\\rarr12}\\frac{14p-28}{p+8}e^{px}="
"=\\frac{-140}{-20}e^{-8x}+\\frac{140}{20}e^{12x}=7e^{-8x}+7e^{12x}"
Answer: "y(x)=7e^{(-8x)}+7e^{(12x)}"
Comments
Leave a comment